2015
DOI: 10.1007/s00520-015-2934-z
|View full text |Cite
|
Sign up to set email alerts
|

The kitchen as therapy: qualitative assessment of an integrative cuisine workshop for patients undergoing chemotherapy

Abstract: Chemotherapy-treated patients participating in an integrative cuisine workshop program showed improved QOL outcomes, specifically GI and emotional-related symptoms, and a reduction in nutritional and functional concerns. Increased knowledge and awareness of nutrition and supplement use ultimately resulted in implementation of the CIM recommendations by patients at home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…We chose the observational study design because we aimed not to impact our day care clinic program to maintain a high external validity of the results. Ben‐Arye et al used qualitative and mixed‐methods study designs to be able to distinguish better between non‐specific and specific effects of CIM interventions . These integrative oncology studies with controlled nonrandomized design showed the impact of individualized and group interventions …”
Section: Discussionmentioning
confidence: 99%
“…We chose the observational study design because we aimed not to impact our day care clinic program to maintain a high external validity of the results. Ben‐Arye et al used qualitative and mixed‐methods study designs to be able to distinguish better between non‐specific and specific effects of CIM interventions . These integrative oncology studies with controlled nonrandomized design showed the impact of individualized and group interventions …”
Section: Discussionmentioning
confidence: 99%
“…CIM may lead not only to a reduction in specific symptoms (e.g., sleep), it may also improve general wellbeing, as was measured by global health status/ QOL and social functioning. Earlier research of this patient population showed that a patient-tailored CIM approach can impact both specific and non-specific outcomes [24]. Non-specific effects include eliciting empathy among the CIM practitioners, enhancing a patient's sense of confidence, inducing a feeling of "togetherness" and "uniqueness," and invoking an internal process targeted at increasing patients' emotional resilience and empowerment [25].…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of these centers (six of 10), guidance on the use of herbal medicine is provided either by an integrative physician or by a naturopath working with a multidisciplinary team of practitioners. At the Bnai Zion Medical Center, an ongoing discourse on the use of herbal medicine by patients takes place directly with the pharmacist, while at the Lin Medical Center the integrative physician consultation addresses the use of herbal medicine within a multimodal context which includes dietary changes, with patients offered active participation in an integrative oncology cuisine workshop [76].…”
Section: Integrative Models For Guiding Oncology Patients On the Use Of Herbal Medicinementioning
confidence: 99%